Barriers to Classroom Communication - Tulsi, P. K. (Journal of Engineering Education Transformations, 2000)
Communication is an integral part of teaching-learning process and its effectiveness is one of the factors which determines the degree to which the intended learning outcomes will be achieved. The process of communication is not always free from hindrances. There are a number of factors related to teacher, message, methods and media, students and learning environment that act as barriers in the process of classroom communication and reduce its effectiveness. These barriers need to be eliminated to increase effectiveness of classroom communication.